Examining Students’ Perception of Using Crowdsourcing based Mobile Apps for Environmental Education and Research Experiences. (International Conference on Computers in Education, 2016)
In the context of complex environmental problems facing societies, it is desirable to enhance public awareness of environmental issues. In response to this challenge, environmental education is an integral part of curriculum utilized at all levels of education, including universityeducation. Environmental education (EE) is now considered to be the most prominent instrument to influence human behaviour towards more environmentally sustainable patterns. However, it is often criticized for being reductionist and empirical and thus not optimal for training next generation of students who are expected to formulate solutions to complex, interdisciplinary environmental issues. We propose that new technologies (crowdsourcing apps) that are being used in research settings to solve interdisciplinary problems may also be used for experiential learning of environmental science. New technologies and growth of digital media are profoundly affecting today’s university students. So, in view of the pervasiveness of new mobile technologies in today’s life and learning, it is essential to lead the instructional process with integrating mobile technology in developing students’ educational and research experiences. In so doing successfully, it is imperative to know the perception of students who are the real and prime users and beneficiary of such approach. Henceforth, the centre of attention of this paper is to investigate university students’ perception and effectiveness of a crowdsourcing based mobile App for environmental education and research. The specific topic considered is land use and land cover change due to human activity. The students were provided with hands on ‘experience of the Land Use Land Cover mobile application.Survey method was used to collect the data.The study reports that the students have a positive perception regarding the use of mobile application, based on the Open Data Kit (ODK), along with the Google Earth Engine (GEE) in implementing experiential learning approach for environmental education and research.